Coyotes - Lepthien, Emilie U. (Emilie Utteg) (Chicago : Childrens Press, 1993)
Discusses the physical characteristics, habits, range, diet, and social nature of coyotes.
Includes index.
Keywords: Coyote -- Juvenile literature; Coyote